Effective suppression of current collapse in both E- and D-mode AlGaN/GaN HEMTs on Si by [(NH4)2Sx] passivation - Vicknesh, Sahmuganathan (2013)
An effective suppression of drain current collapse was realized in both Enhancement (E)-mode and Depletion (D)-mode AlGaN/GaN High-electron-mobility-transistors (HEMTs) on 4-inch Silicon (111) by ammonium sulfide [(NH4)2Sx] passivation. The current collapse was studied using the pulsed current-voltage characteristics with the pulse width of 200 ns and pulse period of 1 ms. With reference to the AlGaN/GaN HEMTs without sulfur passivation, about 30% of the drain current collapse was suppressed for drain quiescent biases of 25 to 30 V. Obtaining low current collapse is essential to demonstrate high power GaN HEMTs.